PENGARUH KOORDINASI TERHADAP EFEKTIVITAS PENERTIBAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) PABRIK DI KAWASAN TIMUR KABUPATEN BANDUNG (STUDI PADA BADAN PENGELOLAAN LINGKUNGAN HIDUP DAERAH KABUPATEN BANDUNG) - Anya Risnawati Soerya Putri (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Background problem in this research is not yet effectively curbing IPAL factory in Eastern Kabupaten Bandung. Based on the phenomenon, researchers suspect that the issue is affected by thevariable coordination. Based on these problems, formulation of the problem posed is: „the influenceof coordination against the effectiveness of curbing Waste water management Plant Installations inEastern Kabupaten Bandung“.Analysis of problem of research done using theory approach to coordination of Erliana and Eviany(2014: 44) defines coordination is an attempt to synchronize, balancing and directs the parties concernedto be able to integrate perception together in an activity to achieve common interests.The methods used in this research is a survey method eksplanatif (explanatory survey method)while the source data collection using the study of librarianship and field studies that include: the now,observation, and interviews. Sample withdrawal technique used is a simple random sample (SimpleRandom Sampling). As for the data analysis technique used is a simple linear regression.Based on the results of the data processing is done the results obtained indicate the existenceof a positive and significant relationship between coordination against the effectiveness of curbingIPAL factory in Eastern Kabupaten Bandung. Thus the hypothesis presented in this research tested theempirical basis.